Microheliella maris possesses the most gene-rich mitochondrial genome in Diaphoretickes - Yazaki, Euki; Yabuki, Akinori; Nishimura, Yuki; Shiratori, Takashi; Hashimoto, Tetsuo; Inagaki, Yuji (Frontiers in Ecology and Evolution, 2022)
The mitochondrial genome is very diverse, but its evolutionary history is unclear due to the lack of efforts to sequence that of protists (unicellular eukaryotes), which cover a major part of the eukaryotic tree. Cryptista comprises cryptophytes, goinomonads, kathablepharids, and Palpitomonas bilix and their mitochondrial genomes (mt-genomes) are characterized by various gene contents, particularly the presence/absence of an ancestral (bacterial) system for the cytochrome c maturation system. To shed light on mt-genome evolution in Cryptista, we report the complete mt-genome of Microheliella maris, which was recently revealed to branch at the root of Cryptista. The M. maris mt-genome was reconstructed as a circular mapping chromosome of 61.2 kbp with a pair of inverted repeats (12.9 kbp) and appeared to be the most gene-rich among the mt-genomes of the members of Diaphoretickes (a mega-scale eukaryotic assembly including Archaeplastida, Cryptista, Haptista and SAR) studied so far, carrying 53 protein-coding genes. With this newly sequenced mt-genome, we inferred and discussed the evolution of the mt-genome in Cryptista and Diaphoretickes.